STUDI DESKRIPSI SISTEM PERPARKIRAN DI GALERIA MALL YOGYAKARTA - Tryas Purnama, Retna Hidayah (Universitas Negeri Yogyakarta, 2015)
ABSTRACTThis study is aimed to describe the eligibility of parking system at Galeria Mall Yogyakarta inparking vehicle based on the standard of the Director General of Land Transportation andNAASRA. The subjects of this study are parking spaces at Galeria Mall Yogyakarta, located onProf.Ir.Yohanes Street. The object of this study is the number of parking spaces available,patterns and dimensions of the parking space, the dimensions of crossing tracks. The datacollection is done by conducting observation and field documentation. The findings of this studywhich have been conducted indicate that: 1) In terms of quantity, the capacity of car parkingspaces: providing only 69% (149 units) out of 214 units that do not meet the standards ofcalculation of Director General of land transportation, worth 2.8 / 100m² from 5.5/100m² so itdoes not meet the NAASRA standards. While motorcycle parking space capacity provides106% (408) out of 385 units so that it meets the standards of calculation. 2) In terms of qualityof SRP car parking area meets the standards: the parking angle and the parking spaces areeffective, Modules, Bp, Lp. SRP B1 floor car area meets the standards: the parking angle andthe parking spaces are also effective, car area on Bp, Lp. SRP B2 Floor meets the standards:the parking angle and the parking spaces are effective (C1, C2, C3), module, the furthest widthof parking space (C1, C2, C3), Bp (C1, C3), Lp (C1, C2, C3). SRP Floor B2 motorcycle areameets the standards: the parking angle and the parking spaces are effective.Keywords: Dimension, Crossing Track, Capacity, Parking Space, SRP